FIGO good practice recommendations on the importance of registry data for monitoring rates and health systems performance in prevention and management of preterm birth. Issue 1 (14th September 2021) - Frøen, J. Frederik; Bianchi, Ana; Moller, Ann‐Beth; Jacobsson, Bo; ,
Abstract: FIGO calls for strengthening of health information systems for reproductive, maternal, newborn, and child health services, co‐designed with users, to ensure the timely accessibility of actionable high‐quality data for all stakeholders engaged in preventing and managing preterm birth consequences. FIGO calls for strengthening of investments and capacity for implementing digital registries and the continuity of reproductive, maternal, newborn, and child health services in line with WHO recommendations, and strengthening of the science of implementation and use of registries—from local quality improvement to big data exploration. Synopsis: Effective preterm birth prevention needs strengthened health information systems for maternal and child health services, co‐designed with users, to ensure accountability and actionable high‐quality data for all stakeholders.